Polymerization Kinetics, Biodegradation and pH-Responsive Behavior of Poly[(Citric Acid-co-PEG-400)-Ran-(Glycerol)] - Matin, M. Abdul; Mahmud, Abu; Islam, M. Nurul; Khatun, Anjuman Ara; Chowdhury, Monishita Nuzhat (Journal of Composites and Biodegradable Polymers, 2018)
Poly[(citric acid-co-PEG-400)-ran-(glycerol)] was synthesized in a vacuum reaction vessel in presence of p-toluene sulphonic acid as catalyst. Synthesized co-polyester was characterized by its glass transition temperature (Tg), FTIR spectrum, elemental analysis and equilibrium swelling behaviors in water and in ethanol. Polymerization kinetics of the said copolymer was figured out. Biodegradation nature was monitored following simple soil burial test and microbial degradation study using the bacterium Bacillus subtilis inoculums. Hydrolytic degradation study reveals that the polymer remains almost intact in acid buffer solution of pH 1.2 but was gradually degraded in phosphate buffer solution of pH 7.4 at 37˚C. Because of having such pH responsive behavior, this co-polyester could be an ideal future candidate for the site targeted drug delivery medium.